Destabilization of lubrication oil micropool under charged conditions. Issue 1 (9th January 2017) - Xie, Guoxin; Cui, Ziyi; Si, Lina; Guo, Dan
Abstract : Purpose: This paper aims to introduce a series of experimental results which are the extension of our previous novel observations (Xie et al., Soft Matter, 2011), which could be helpful for revealing the lubrication failure mechanism in bearings when they are exposed to an electrical environment. Design/methodology/approach: An experimental apparatus where a ball was in contact with a glass disk coated with a semi-reflective chromium layer. A small volume of oil droplet was put into the microgap of the ball-disk contact. Then, a potential was applied onto the oil micropool formed by the droplet surrounding the contact region. Findings: It has been found that destabilization of the low-conducting oil micropool around the contact region could be induced after applying a potential. Thin oil films could be drained out of the oil pool and spread on the tribopair surfaces, resulting in the depletion of the oil pool. When the applied potential was increased, the occurrence of spreading would be easier and its development would be more obvious. In contrast, the electrospreading behavior would be suppressed when the oil viscosity, contact load and oil pool size were increased. Thermocapillary force due to thermal effect as a result of the current flow near the oil pool border has been proposed as the main driving force for the spreading behavior. The influences of the operating parameters have been ascribed to the change of the electric current near the oil pool border as well as the corresponding variations in the temperature rise and the surface tension of the oil pool. Originality/value: This is the first study to directly observe that the lubricant oil micropool around the contact region could deplete after applying a potential, potentially resulting in oil starvation in the contact region.